High-Affinity Human Anti-c-Met IgG Conjugated to Oxaliplatin as Targeted Chemotherapy for Hepatocellular Carcinoma - Ma, Yilan; Zhang, Mingjiong; Wang, Jiayan; Huang, Xiaochen; Kuai, Xingwang; Zhu, Xiaojuan; Chen, Yuan; Jia, Lizhou; Feng, Zhenqing; Tang, Qi; Liu, Zheng (Frontiers in Oncology, 2019)
Hepatocellular carcinoma (HCC) is one of the most mortality-causing solid cancers globally and the second largest cause of death among malignancies. Oxaliplatin, a platinum-based drug, has been widely utilized in the treatment of malignancies such as colorectal cancer and hepatocellular carcinoma, yet its usage is limited because of severe side effects of cytotoxicity to normal tissues. c-Met, a receptor tyrosine kinase, is expressed aberrantly on the surface of HCC. The purpose of this study was to synthesise a humanized antibody against c-Met (anti-c-Met IgG) and conjugate it to oxaliplatin to develop a novel antibody-drug conjugate (ADC). Anti-c-Met IgG was detected to be loaded with ~4.35 moles oxaliplatin per mole of antibody. ELISA and FCM confirmed that ADC retained a high and selective binding affinity for c-Met protein and c-Met-positive HepG2 cells. In vitro, the cytotoxicity tests and biological function assay indicated that ADC showed much higher cytotoxicity and functioning in c-Met-positive HepG2 cells, compared with shMet-HepG2 cells expressing lower levels of c-Met. Furthermore, compared with free oxaliplatin, ADC significantly improved cytotoxicity to c-Met-positive tumours and avoided off-target cell toxicity in vivo. In conclusion, by targeting c-Met-expressing hepatoma cells, ADC can provide a platform to reduce drug toxicity and improve drug efficacy in vitro and in vivo.